HHV-8-negative multicentric Castleman disease presenting as a crescentic immune complexes membranoproliferative glomerulonephritis. Issue 1 (6th January 2020) - Nunes, Maria Brito; Rotman, Samuel; Duss, Francois-Regis; Halfon, Matthieu
Abstract : Multicentric Castleman disease is a rare polyclonal lymphoproliferative disorder mainly associated with two renal manifestations: thrombotic microangiopathy and amyloidosis. Nevertheless, we report here a case of human herpes virus-8 negative multicentric Castleman disease with membranous proliferative glomerulonephritis and extracapillary proliferation. A patient was successfully treated with corticosteroids, anti-CD20 and cyclophosphamide therapy.